The Effect of Training and Teaching Experiences on the Performance of Elementary School Teachers: Pengaruh Pelatihan Dan Pengalaman Mengajar Terhadap Kinerja Guru Sekolah Dasar - Erly Rahmawati; Idham Kholid; Riyuzen Riyuzen (Journal of Contemporary Islamic Education, 2021)
The study aims are: 1) to explain the effect of training on teachers’ performance, 2) to explain the effect of teaching experience on teachers’ performance, and 3) to explain the effect of training and teaching experience on teachers’ performance. The study population are all elementary school teachers in the District of Lemong Pesisir Barat consist 179 people, while the sample in this study amounted to 64 respondents. This study uses a quantitative approach to the type of verification research and uses data collection techniques, namely interviews and questionnaires. The analytical research are descriptive statistical analysis and inferential statistical analysis. The results showed that 1) Training partially had a positive and significant effect on teachers’ performance, 2) teaching experience partially had a positive and significant effect on teachers’ performance, and 3) Training and teaching experience simultaneously had a positive and significant effect on teachers’ performance.